Potential for alcohol and drug interactions in older adults: evidence from the Irish longitudinal study on ageing - KENNY, ROSE; Henman, Martin (My University, 2014)
Background Older adults are susceptible to adverse effects from the concomitant use of prescription medications and alcohol. This study estimates the prevalence of exposure to alcohol interactive (AI) medications and concomitant alcohol use by therapeutic class in a large, nationally representative sample of older adults. Methods Cross-sectional analysis of a population based sample of older Irish adults aged ≥60 years using data from The Irish Longitudinal Study on Ageing (TILDA) (N = 3,815). AI medications were identified using Stockley’s Drug Interactions, the British National Formulary and the Irish Medicines Formulary. An in-home inventory of medications was used to characterise AI drug exposure by therapeutic class. Self-reported alcohol use was classified as non-drinker, light/moderate and heavy drinking. Comorbidities known to be exacerbated by alcohol were also recorded (diabetes mellitus, hypertension, peptic ulcer disease, liver disease, depression, gout or breast cancer), as well as sociodemographic and health factors. Results Seventy-two per cent of participants were exposed to AI medications, with greatest exposure to cardiovascular and CNS agents. Overall, 60% of participants exposed to AI medications reported concomitant alcohol use, compared with 69.5% of non-AI exposed people (p < 0.001). Almost 28% of those reporting anti-histamine use were identified as heavy drinkers. Similarly almost one in five, combined heavy drinking with anti-coagulants/anti-platelets and cardiovascular agents, with 16% combining heavy drinking with CNS agents. Multinomial logistic regression showed that being male, younger, urban dwelling, with higher levels of education and a history of smoking, were associated with an increased risk for concomitant exposure to alcohol consumption (both light/moderate and heavier) and AI medications. Current smokers and people with increasing co-morbidities were also at greatest risk for heavy drinking in combination with AI medications. Conclusions The concurrent use of alcohol with AI medications, or with conditions known to be exacerbated by alcohol, is common among older Irish adults. Prescribers should be aware of potential interactions, and screen patients for alcohol use and provide warnings to minimize patient risk.
PUBLISHED
Keywords: Aged; Alcohol drinking/epidemiology; Alcohol interactive medications; Drug interactions; Ageing; Neuroscience; PHARMACY PRACTICE